Factors Impacting Satisfaction and Continuance Intention with E-Learning of Students Majoring in Radio and Television Director at Private Art Schools in Western China - Zhuan, Wang (Scholar: Human Sciences, 2025)
Purpose: This study aims to explore the factors impacting student satisfaction and continuance intention to use online learning among Radio and Television Directing majors in private art schools in western China. The key variables are perceived ease of use, perceived usefulness, informative quality, service quality, system quality, satisfaction and continuance intention. Research Design, Data, and Methodology: A quantitative approach was employed in this study. Data was collected from students majoring in Radio and Television Directing at three private art schools in western China. Confirmatory factor analysis (CFA) was used to assess the reliability and discriminant validity of the conceptual framework model. Structural equation modeling (SEM) was utilized to examine the relationships and influences among the different variables. Results: The research findings indicate that service quality is the most significant factor influencing student satisfaction with online learning, followed by usefulness, ease of use, information quality, and system quality. Furthermore, perceived satisfaction has a positive and significant impact on students' continued intention to use online learning. Conclusions: Educational institutions should focus on improving their electronic learning platforms, while policymakers should develop targeted policies and measures. Additionally, educational content can be tailored based on these research findings to cater to the diverse needs of students.